SASP‐induced macrophage dysfunction may contribute to accelerated senescent fibroblast accumulation in the dermis. Issue 1 (20th December 2020) - Ogata, Yuichiro; Yamada, Takaaki; Hasegawa, Seiji; Sanada, Ayumi; Iwata, Yohei; Arima, Masaru; Nakata, Satoru; Sugiura, Kazumitsu; Akamatsu, Hirohiko
Abstract: Recently, increasing attention has been paid to senescence‐associated secretory phenotype (SASP), a phenomenon that senescent cells secrete molecules such as inflammatory cytokines and matrix metalloproteinases (MMPs), due to its noxious effects on the surrounding tissue. Senescent cells in the blood and liver are known to be properly depleted by macrophages. In the dermis, accumulation of senescent cells has been reported and is thought to be involved with skin ageing. In this study, to elucidate the clearance mechanism of senescent cells in the dermis, we focused on macrophage functions. Our co‐culture experiments of senescent fibroblasts and macrophages revealed a two‐step clearance mechanism: first, TNF‐α secreted from macrophages induces apoptosis in senescent fibroblasts, and then, dead cells are phagocytosed by macrophages. Furthermore, it was suggested that SASP factors suppress both of the two steps of the senescent cell clearance by macrophages. From these findings, normally senescent cells in the dermis are thought to be removed by macrophages, but when senescent cells are excessively accumulated owing to oxidative stress, ultraviolet (UV) ray or other reasons, SASP was suggested to suppress the macrophage‐dependent clearance functions and thereby cause further accumulation of senescent cells.